Visible to Mid-Infrared Frequency Comb Generation with Thick Room-Temperature Sputtered Silicon Nitride - Alabbadi, Abdullah; Kheyri, Masoud; Zhang, Shuangyou; Bi, Toby; Del'haye, Pascal (2025 Conference on Lasers and Electro-Optics, CLEO 2025, 2025)
We use 1-μm-thick silicon-nitride waveguides made by reactive ion sputtering to generate multi-octave frequency combs spanning from 600 nm to 4.2 μm. The broad bandwidth is enabled by dispersion engineering of large-cross-section silicon-nitride waveguides.
CRIS-Team Scopus Importer:2025-11-21